Social mobilizations and forms of peasant struggle in the district of Cajibío (Cauca): 1990-2006 - Lugo Vivavas, Diego Andrés (Sociedad y Economía, 2010)
The purpose of this article is to describe social mobilizations and forms of peasant struggle developed by peasant population in the municipality of Cajibío (Cauca) between 1990 and 2006. We will present an analysis of the most representative types of protest advanced by a population that in different circumstances has decided to move either to the defense of better living conditions or to the respect and recognition of rights considered fundamentals. To this end, we have resorted to the use of documentary sources located in printed and electronic archives in Cajibío, Cali, and Bogotá. We will pay special attention to phenomena related with land occupations and affectations, blocked roads, and forced mass displacement, given its intensity, frequency, and impact on the region.